CLIMATE GAMES: WHO’S ON FIRST? WHAT’S ON SECOND? - Insley, Margaret; Forsyth, Peter (L'Actualité économique, 2019)
We study four different climate change games and compare with the outcome of choices by a Social Planner. In a dynamic setting, two players choose levels of carbon emissions. Rising atmospheric carbon stocks increase average global temperature which damages player utilities. Temperature is modelled as a stochastic differential equation. We contrast the results of a Stackelberg game with a game in which both players act as leaders (a Leader-Leader, or Trumpian game). We also examine an Interleaved game where there is a significant time interval between player decisions. Finally we examine a game where a Nash equilibrium is chosen if it exists, and otherwise a Stackelberg game is played. One or both players may be better off in these alternative games compared to the Stackelberg game, depending on state variables. We conclude that it is important to consider alternate game structures in examining strategic interactions in pollution games. We also demonstrate that the Stackelberg game is the limit of the Interleaved game as the time between decisions goes to zero.